Investigasi pola XRD dan ukuran kristal pada TiO2 terdoping vanadium menggunakan aplikasi VESTA - Elfrida Dwi Saputri; Rahmawati Munir; Adrianus Inu Natalisanto (Progressive Physics Journal, 2022)
Visualization of crystal structure and simulation of X-ray diffraction patterns of TiO2 (Titanium dioxide) was successfully performed by VESTA application. The purpose of this research is to obtain the relation of lattice parameter and composition to the diffraction pattern. The program on VESTA needs several input parameters that can be found on Crystallography Open Database (COD). The obtained output of the VESTA application are in the form of crystal structure and diffraction pattern graph. The data obtained by VESTA can be used to estimate the size of the crystal. The result showed that TiO2 has a tetragonal shape crystal structure. The addition of dopant such as Vanadium does not change the crystal structure and does not change the peak position of diffraction pattern graph.